Análise de custo exergético de ciclo híbrido para queima de lixo urbano - Mollica, Gustavo José Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The increasing generation of municipal solid waste (MSW) is one of the biggest problems of society nowadays. Incorrect disposition of this material causes major impacts to the human health e also to the environment. Incineration of MSW with energy recovery in plants know as Waste to Energy (WTE) is one of the main ways found by many countries to try and soften this situation. Those plants have a very high operation and maintenance cost, though, which make developing countries as Brazil to give preference for current means of waste disposition. Another big problem faced by society and that has also been very discussed in the last decades is the pollutant gas emissions, mostly the ones responsible for the greenhouse effect, launched in the atmosphere in the burning of fossil fuels. To control these pollutant emissions international treaties as the Kyoto protocol have introduced the concept of carbon tax, a tax to be charged for the emission of carbon dioxide, which has already been used in many countries. The objective of this study is to apply the carbon exergy tax method in WTE plants to investigate its application and try and propose ways that encourage the utilization of this technology. The carbon exergy tax method utilizes concepts brought from Thermoeconomics and bases itself in the efficiency and type of fuel used in the cycles studied to obtain a value for the carbon tax, that differently from current taxes, is not based on political considerations. For that it was used the theory of exergetic cost to calculate the exergetic costs e subsequent values of exergy lost to the environment and destroyed exergy. From the results found it was possible to propose a modification to the method to consider the environmental aspect of waste's destruction, in this way promoting the destruction of this material. The results found promote the... (Complete abstract, click electronic access below)

A geração crescente de resíduos sólidos urbanos é um dos maiores problemas da sociedade atualmente. A disposição incorreta deste material causa grandes impactos para a saúde do ser humano e para o meio ambiente. Uma forma encontrada por muitos países para amenizar esta situação está na incineração deste material com aproveitamento energético em plantas conhecidas como WTE (Waste to Energy). Porém, estas plantas têm custos elevados, o que faz com que países em desenvolvimento como o Brasil ainda prefiram os meios atuais de disposição destes resíduos. Outro problema enfrentado pela sociedade e muito discutido atualmente é a emissão de gases causadores do efeito estufa na queima de combustíveis fósseis. Como uma forma de controlar a emissão desses poluentes, tratados internacionais, como o de Quioto, introduziram o conceito de taxação do carbono emitido, que vem sendo utilizado em muitos países. O objetivo deste trabalho é aplicar o método da taxa de exergia de carbono em plantas WTE a fim de investigar sua aplicação e propor meios que incentivem a utilização desta tecnologia. O método da taxa de exergia de carbono utiliza a Termoeconomia e baseia-se na eficiência e tipo de combustível utilizado nos ciclos estudados a fim de se obter um valor de taxa de carbono que diferentemente das taxas atuais não se baseia em considerações políticas. Para isto, utilizou-se a teoria do custo exergético para cálculo dos custos exergéticos unitários e consequente cálculo das exergias perdidas para o ambiente e exergias destruídas. A partir dos resultados encontrados, foi proposta uma modificação no método de modo a considerar o caráter ambiental da destruição do resíduo sólido urbano, incentivando a destruição desse material. Os resultados encontrados promovem o uso desta tecnologia frente às que ... (Resumo completo clicar acesso eletrônico abaixo)
Hybrid cycle exergy cycle cost analysis for urban waste burning
Keywords: Resíduos sólidos; Incineradores; Termoeconomia; Incinerators